Control and decision strategies in wastewater treatment plants for operation improvement - Santín, Ignacio; Pedret, Carles; Vilanova, Ramón (Springer, 2016)
This book examines the operation of biological wastewater treatment plants (WWTPs), with a focus on maintaining effluent water quality while keeping operational costs within constrained limits. It includes control operation and decision schemes and is based on the use of benchmarking scenarios that yield easily reproducible results that readers can implement for their own solutions. The final criterion is the effect of the applied control strategy on plant performance - specifically, improving effluent quality, reducing costs and avoiding violations of established effluent limits. The evaluation of the different control strategies is achieved with the help of two Benchmark Simulation Models (BSM1, BSM2). Given the complexity of the biological and biochemical processes involved and the major fluctuations in the influent flow rate, controlling WWTPs poses a serious challenge. Further, the importance of control goal formulation and control structure design in relation to WWTP process control is widely recognized. Of particular interest are the regulations governing the compliance with effluent criteria. Authorities measure compliance with these criteria on the basis of long or short timeframes, and the legal constraints imposed on effluent pollutant concentrations are among the most essential aspects of control structures for WWTPs. This book explores all these facets in detail.
Keywords: Sewage disposal plants -- Automation.; Sewage disposal plants -- Decision making.; elektronické knihy; electronic books